Causes of the exceptionally high number of fatalities in the Ahr valley, Germany, during the 2021 flood - B. Rhein; B. Rhein; H. Kreibich (Natural Hazards and Earth System Sciences)
Over the last 40 years (1980–2020), 159 people died in inland floods in Germany. The flood of 2021 caused 190 flood fatalities in Germany, 134 of them in the Ahr valley. We investigate what made this event so deadly in order to help improve flood risk management and prevent future fatalities. A comprehensive analysis of the factors influencing the occurrence of fatalities is carried out on the basis of the death investigation files of the public prosecutor's office. This unprecedented flash flood was characterised by high water levels and high flow velocities. The extent of inundation in 2021 far exceeded the official hazard map for the extreme flood scenario. Additionally, early warning and evacuation were inadequate, so many people were surprised by the flash flood. Of the total fatalities, 75 % occurred outside of the mapped hazard zones. Particularly dangerous places were campsites, cellars and basement flats, but many people died on the ground floor (37 %) or outside on the street (18 %). The elderly above 60 years of age (78 %) and those with mobility or cognitive impairments (16 %) were particularly vulnerable. No gender-specific differences in vulnerability were observed. Thus, the main causes for the exceptionally high number of fatalities were the extreme severity of the flood and its underestimation by the population and authorities, as well as inadequate early warning and evacuation. Consequently, public understanding of the particular danger posed by flash floods must be improved, as must the development and presentation of worst-case scenarios in hazard maps. Additionally, impact forecasting can significantly improve emergency management of such unprecedented floods. Specific recommendations for disaster management are (1) that in the event of such extreme flash floods, the warning messages must focus on saving human lives – i.e. those at risk must be advised to move to safe places, e.g. to the upper floors, instead of trying to save belongings – and (2) evacuations must be initiated in good time, especially where flooding of the ground floor with high water levels is to be expected, paying particular attention to the safety of the elderly and people with limited mobility.